Connecting the Dots and Merging Meaning: Using Mixed Methods to Study Primary Care Delivery Transformation. (1st November 2013) - Scammon, Debra L.; Tomoaia‐Cotisel, Andrada; Day, Rachel L.; Day, Julie; Kim, Jaewhan; Waitzman, Norman J.; Farrell, Timothy W.; Magill, Michael K.
Abstract : Objective: To demonstrate the value of mixed methods in the study of practice transformation and illustrate procedures for connecting methods and for merging findings to enhance the meaning derived. Data Source/Study Setting: An integrated network of university‐owned, primary care practices at the University of Utah (Community Clinics or CCs). CC has adopted Care by Design, its version of the Patient Centered Medical Home. Study Design: Convergent case study mixed methods design. Data Collection/Extraction Methods: Analysis of archival documents, internal operational reports, in‐clinic observations, chart audits, surveys, semistructured interviews, focus groups, Centers for Medicare and Medicaid Services database, and the Utah All Payer Claims Database. Principal Findings: Each data source enriched our understanding of the change process and understanding of reasons that certain changes were more difficult than others both in general and for particular clinics. Mixed methods enabled generation and testing of hypotheses about change and led to a comprehensive understanding of practice change. Conclusions: Mixed methods are useful in studying practice transformation. Challenges exist but can be overcome with careful planning and persistence.